2021
DOI: 10.33963/kp.a2021.0005
|View full text |Cite
|
Sign up to set email alerts
|

Patients scheduled for TAVI tend to form abnormal fibrin clots more resistant to lysis: the impact of age

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“… 30 Our research demonstrated that patients with stages 3-4 CKD, compared to patients with eGFR ≥ 60 mL/min/1.73 m 2 are characterized by higher fibrinogen levels, higher endogenous thrombin potential as a measure of thrombin formation, lower fibrin clot permeability as a measure of fibrin network density, and longer clot lysis time. 15 The prothrombotic fibrin clot phenotype reported in patients with several diseases associated with prothrombotic tendency 31 - 33 has also been observed in those with AF and CKD in relation to elevated NT-proBNP. 34 …”
Section: Prediction Of Major Adverse Events In Chronic Kidney Diseasementioning
confidence: 91%
“… 30 Our research demonstrated that patients with stages 3-4 CKD, compared to patients with eGFR ≥ 60 mL/min/1.73 m 2 are characterized by higher fibrinogen levels, higher endogenous thrombin potential as a measure of thrombin formation, lower fibrin clot permeability as a measure of fibrin network density, and longer clot lysis time. 15 The prothrombotic fibrin clot phenotype reported in patients with several diseases associated with prothrombotic tendency 31 - 33 has also been observed in those with AF and CKD in relation to elevated NT-proBNP. 34 …”
Section: Prediction Of Major Adverse Events In Chronic Kidney Diseasementioning
confidence: 91%
“…In cancer patients, common comorbidities which typically affect older subjects prone to malignant diseases may have some impact on fibrin clot properties. There is strong evidence regarding prothrombotic fibrin clot properties in patients with cardiovascular disease 65 66 or prior VTE 67 as well as those with type 2 diabetes 68 or advanced kidney disease. 69 Taken together, comorbidities associated with prothrombotic fibrin clot phenotype 66 may heighten the risk of CAT, though available data supporting this concept are scarce.…”
Section: Fibrin Clot Properties In Specific Diseasesmentioning
confidence: 99%
“…Calibrated Automated Thrombography (CAT; Thrombinoscope BV, Maastricht, the Netherlands), was used to measure endogenous thrombin potential (ETP). 22 The fluorometer (Ascent Reader, Thermolabsystems OY, Helsinki, Finland) was used to generate the area under the curve at 37°C. 20 µL of tissue factor (TF)-based activator (PPP Reagent containing 5 µmol/L recombinant TF and 4 µmol/L phospholipid vesicles; Diagnostica Stago) and FluCa solution (Diagnostica Stago) was added to 80 µL platelet-poor plasma.…”
Section: Endogenous Thrombin Potential (Etp)mentioning
confidence: 99%